In-vitro screening of Iranian Landraces (Triticumaestivum L.) at the seedling stage for water stress tolerance using Polyethylene glycol (PEG 6000 - Kaur, Amandeep; Sarlach, Rashpal Singh (International Journal of Environment, Agriculture and Biotechnology, 2020)
To understand, the parameters in wheat which can be used as criteria for drought tolerance, the present investigation was carried out on eight genotypes to an optimum dose of Polyethylene glycol (PEG6000) for water stress tolerance at germination and seedling stage. The experiment was conducted in the Department of Plant Breeding and Genetics with three replications under completely Randomized Design,7 different concentration of Polyethylene glycol that were 0, 6%, 8%, 10%,12%, 14% 16% and 18% used in this experiment which were prepared according to weight by volume method. There was a significant reduction in seedling parameters with an increasing concentration of Polyethylene glycol. Based upon the vigor index low treatment of polyethylene glycol decreased the seedling parameters to a lesser extent than high concentration. The maximum difference in all seedling parameters was observed at 14% but as the concentration of polyethylene glycol increased (16% and 18%) there was a greater reduction in the root, shoot length and vigor index as compared to 14% of Polyethylene glycol which had an intermediate effect on seedling parameters. Identifying the drought-tolerant wheat genotypes during the seedling stage by in-vitro screening is a physiological approach which assists breeder for rapid selection of genotypes. Highlights • Reduction in seedling parameters with increasing concentration of Polyethylene glycol • Water stress-tolerant landraces have maximum vigor index • For in-vitro screening, the moderate concentration of Polyethylene glycol should be used